An experimental investigation on improvement of concrete serviceability by using ferro sialate based bacterial concrete development. (2022) - Dharmaraj, R.; Logeswaran, S.; Narayanan, Karuppasamy; Ramalingam, Malathy; Chadra Prakash, V.; Rajalinggam, Pon
Abstract: GPBC (Geo-Polymer Bacterial Concrete) is a recent developing green concrete which over comes the drawback of emission of carbon-di-oxide and the crack damage in the concrete structures. This project describes the compressive strength and flexural properties of GPBC. The purpose is to incorporate the healing agents into the geo-polymer concrete which makes the cracks heal from inside. Sodium silicate and sodium hydroxide are the alkaline solutions which activates the cementitious materials for the process of geo-polymerization. The bacillus megaterium and bacillus subtilis are the two species which is selected with a 0gm/l, 100gm/1, 200gm/1 as a varying proportion in this study to act as the healing agent and calcium lactate acts as organic precursor, incorporated into the concrete by the direct mixing technique. The mechanical properties such as compressive strength and Flexural behavior of reinforced concrete slab specimens are planned. The 28 days of compressive strength for cubes is done to indicate the strength property of geo-polymer concrete in which the GGBS and Fly ash acts as the strength governing factor. These experimental results of deflection values are compared with corresponding load vs deflection curves are plotted for the experimental studies.